Sosialisasi Anak dalam Majalah “Bobo” - Chaerowaty, Dede Lilis (FIkom Unisba, 2007)
As pointed out by Piaget, mass media products are not only an entertainment medium for audience. Mass media—especially for children—become a source of reference. Children learn through media in their developmental age. Media provided materials and children inherited cultural values from media through a series of socialization stages. Bobo, a national children magazine, did the same thing. An analysis toward issue coverage of Bobo revealed that the magazine reported international events more than local events. Bobo, therefore, has ignored a chance to supplant Indonesian children with local wisdom. Another finding showed a Bobo’s high tendency to claim children as consumer and purchaser.